2021
DOI: 10.38027/iccaua2021303n7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sustainability for Infection Prevention and Control (IPC) in Healthcare Facilities

Abstract: The emergence of the novel coronavirus, increase in microbial resistance and the scarceness of vaccines for the present pandemic have made it imperative to appraise the link between the sustainable built environment and Infection control as well as the strategies employed during the pre-antibiotic period. This paper aims to identify the nexus between a sustainable built environment and infection control in healthcare facilities with the view of developing guidelines and highlighting the role of architecture in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Effective leadership commitment emerges as essential for motivating and integrating environmental sustainability initiatives in healthcare. As Lee et al and Emmanuel et al demonstrate, leadership involvement at the administrative level is key for driving adoption of sustainable practices, overcoming barriers, and fostering a culture shift [38,41]. Their study underscores that sustainable practices in healthcare settings often require a culture shift that begins at the top, with strong leadership driving change.…”
Section: Leadership and Management In Driving Sustainability Initiativesmentioning
confidence: 93%
See 4 more Smart Citations
“…Effective leadership commitment emerges as essential for motivating and integrating environmental sustainability initiatives in healthcare. As Lee et al and Emmanuel et al demonstrate, leadership involvement at the administrative level is key for driving adoption of sustainable practices, overcoming barriers, and fostering a culture shift [38,41]. Their study underscores that sustainable practices in healthcare settings often require a culture shift that begins at the top, with strong leadership driving change.…”
Section: Leadership and Management In Driving Sustainability Initiativesmentioning
confidence: 93%
“…Among the twelve studies analyzed [33][34][35][36][37][38][39][40][41][42][43][44], in the risk of bias assessment of the included studies, varying degrees of bias risk are observed, reflecting the diversity of study designs (Figure 2). Several studies, such as Lee et al ( 2022 2021) inherently exhibit some concerns regarding randomization but generally show low risk across other bias domains [38].…”
Section: The Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations